Unified synthesis of diverse building blocks for application in the discovery of bioactive small molecules. Issue 38 (20th September 2019) - Rice, Scott; Cox, Daniel J.; Marsden, Stephen P.; Nelson, Adam
Abstract: The synthesis of large numbers of diverse molecular scaffolds with controlled molecular properties is a significant challenge in synthetic organic chemistry. A modular unified synthesis was developed, and was exploited in the synthesis of sixteen diverse three-dimensional scaffolds. The approach exploited two cyclisation precursors to be converted, using a toolkit of cyclisation reactions, into spirocyclic and fused-ring scaffolds. Remarkably, Pd-catalysed aminoarylation of substituted N -Boc-hex-5-enylamine cyclisation precursors to yield N- Boc piperidine-containing scaffolds was successful which was ascribed to a significant Thorpe−Ingold effect. Computational property analysis showed that the decorated scaffolds are shape-diverse, and enable diverse lead-like chemical space to be targeted. Graphical abstract: Image 1 Highlights: Unified synthesis of diverse building blocks. Pd-catalysed aminoarylation yields N- Boc piperidine-containing scaffolds. The decorated scaffolds are shape-diverse, and enable diverse lead-like chemical space to be targeted.